A mixed-methods evaluation of college student and provider perspectives on a smartphone application for help-seeking after violence. Issue 6 (31st August 2021) - Anderson, Jocelyn C.; Pollitt, Erin; Crowley, Joseph; Holbrook, Debra; Draughon Moret, Jessica E.
Abstract: Objective: To elicit feedback on the acceptability, usability, and dissemination options for the bMOREsafe smartphone application (app). Participants: Forty-nine students and six service-providers provided feedback on the bMOREsafe app between April 2015 and March 2016. Methods: Students responded to an anonymous online survey and providers participated in semi-structured interviews. Descriptive and thematic analyses were completed. Results: Students rated the app as useful, however less applicable to themselves and their peers. Students stated they would be most receptive to recommendations about the app from peers and social media. Qualitative data from service providers fell into three main categories: trauma-informed aspects ; inclusivity vs. specificity ; and within an app, language matters . Conclusions: Smartphone technology can provide confidential information and resources to help students make decisions related to sexual assault or intimate partner violence care. While students and providers identified apps as a useful strategy for sharing this information, dissemination challenges remain.